Middle cerebral artery dissection: pathophysiology, diagnosis, and therapeutic options - Yao, Xiangpeng; Yang, Niao; Yan, Nao (Frontiers in Neurology, 2025)
Middle cerebral artery dissection (MCAD) is a rare cerebrovascular disorder that can lead to ischemic stroke or hemorrhagic events. Although its exact incidence remains unclear, the detection rate of MCAD has increased in recent years with advancements in imaging technology. Based on a systematic literature review of MEDLINE/PubMed, the Cochrane Library, Web of Science, and EMBASE, combined with the latest guidelines on intracranial artery diseases and stroke management, this article comprehensively reviews the pathophysiological mechanisms, imaging characteristics, and treatment strategies for MCAD.